2021
DOI: 10.3389/fnins.2021.699948
|View full text |Cite
|
Sign up to set email alerts
|

Mini-Review of Studies Testing the Cardiorespiratory Hypothesis With Near-Infrared Spectroscopy (NIRS): Overview and Perspectives

Abstract: The cardiorespiratory hypothesis (CH) is one of the hypotheses used by researchers to explain the relationship between cardiorespiratory fitness and cognitive performance during executive functions. Despite the indubitable beneficial effect of training on brain blood flow and function that may explain the link between physical fitness and cognition and the recognition of the near-infrared spectroscopy (NIRS) as a reliable tool for measuring brain oxygenation, few studies investigated the CH with NIRS. It is st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 62 publications
(104 reference statements)
0
4
0
Order By: Relevance
“…Another physiological mechanism that may explain the improvement in cognitive vitality is the release of the vascular endothelial growth factor which is a precursor to angiogenesis. Angiogenesis induces an increase in cerebral blood flow which, in turn, ensures a better oxygen supply to the neuronal networks involved in cognitive functions so that they can function better (Albinet et al, 2014;Dupuy et al, 2015;Agbangla et al, 2021). Moreover, these interventions are also capable of reducing oxidative stress (Umegaki et al, 2021) and inflammation (Fedewa et al, 2017;Huang et al, 2021) which can reduce neuronal death and consequently maintain the cognitive functions.…”
Section: Explanations For the Beneficial Effects Of Physical Exercise...mentioning
confidence: 99%
“…Another physiological mechanism that may explain the improvement in cognitive vitality is the release of the vascular endothelial growth factor which is a precursor to angiogenesis. Angiogenesis induces an increase in cerebral blood flow which, in turn, ensures a better oxygen supply to the neuronal networks involved in cognitive functions so that they can function better (Albinet et al, 2014;Dupuy et al, 2015;Agbangla et al, 2021). Moreover, these interventions are also capable of reducing oxidative stress (Umegaki et al, 2021) and inflammation (Fedewa et al, 2017;Huang et al, 2021) which can reduce neuronal death and consequently maintain the cognitive functions.…”
Section: Explanations For the Beneficial Effects Of Physical Exercise...mentioning
confidence: 99%
“…In particular, it was shown that high-fit older adults display higher PFC oxygenation during a cognitive task than low-fit older adults (Albinet et al, 2014;Dupuy et al, 2015), particularly under the highest cognitive load, that is, when the task is very demanding (Agbangla et al, 2019). This higher cerebral oxygenation could be partly linked to a higher O 2 delivery to the brain in high-fit older adults as a high cardiorespiratory fitness can be associated with angiogenesis, enhanced vascular plasticity, and vascular health (Agbangla et al, 2021).…”
mentioning
confidence: 99%
“…In a meta-analysis, Rooks et al (2010) examined the impact of training status on cerebral oxygenation during incremental tests without considering how CRF and training status were measured (i.e., VO 2max or physical activity level). More recently, Agbangla et al (2021) reviewed the impact of CRF on cerebral oxygenation during cognitive tasks. This review examined the effects of CRF level, as determined by direct or estimated measures, on cerebral oxygenation during exercise and cognitive task performance.…”
Section: Effects Of Cardiorespiratory Fitness On Cerebral Oxygenation...mentioning
confidence: 99%
“…For these reasons, fNIRS publications have grown exponentially with many studies focusing on exercise and cognition (Yan et al, 2020). However, few reviews focus on the role of CRF on cerebral oxygenation during cognitive or physical activity and to our knowledge none have examined this systematically (Agbangla et al, 2021).…”
Section: Introductionmentioning
confidence: 99%